DETEKSI DAN CEGAH DINI DALAM PENCEGAHAN KONFLIK SOSIAL BERBASIS AGAMA OLEH BAKESBANGPOL KABUPATEN LOMBOK TIMUR PROVINSI NUSA TENGGARA BARAT - Novita Lestari; Lalu Satria Utama (Journal of Innovation Research and Knowledge, 2025)
Religious-based social conflict in East Lombok Regency is one of the serious challenges that is an important concern for the local government because it has an impact on disrupting social stability, national unity, and community harmony. This has encouraged the local government through the National Unity and Political Agency (Bakesbangpol) to make efforts to detect and prevent early social conflict. Purpose: The purpose of this study was to determine early detection efforts in the prevention of religious-based social conflicts and the obstacles faced by the National Unity and Political Agency of East Lombok Regency. Method: The research method used is descriptive qualitative research method with inductive approach. The data sources in this study are primary and secondary data sources. The data analysis techniques used are data reduction, data presentation, and data verification. Data collection techniques include interviews, observation and documentation. Result: The results showed that the implementation of early detection was still not optimal due to limited intelligence capabilities, low quality of human resources, and community awareness and participation. Conclusion: The implementation of early detection and prevention of Bakesbangpol East Lombok Regency has not been maximized, this is because Bakesbangpol has implemented all indicators that measure the success of prevention and early detection quite well. Researchers recommend intelligence training for members, routine patrols, and continuous socialization to the community as steps to prevent religious-based social conflicts